RESPONSES AND ATTITUDE OF TOURISTS TOWARD THE COVID-19 PANDEMIC: A CASE STUDY OF VIETNAM - Thi Van Hanh NGUYEN (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
World tourism is facing a multitude of global challenges in the event of a world pandemic (Covid-19). The loss of the tourism industry during a pandemic is caused by the drop-off of tourist numbers. Understanding tourist response in the context of various types of crises is important and has several managerial and marketing implications. Through an online survey taken in Vietnam during March 2020, this paper aims at indicating how Vietnamese tourists react to their traveling needs during the time of an epidemic. The result showed that tourists are strongly impacted by the epidemic and are less likely want to take risk of traveling. Their decisions depend on their awareness of risk and preventive measures taken by other tourism stakeholders. Findings from this study brought out some implications for reviving the tourism industry in response to the epidemic. Measures to reassure customers that their holidays are safe will be the ultimate way for the tourism sector to recover